Account Representative Service Quality Dimensions and Compulsory Level of Education Tax on Taxpayer Compliance Personal Person - Hasibuddin Badarullah (Golden Ratio of Taxation Studies, 2022)
The purpose of this study was to analyze the effect of the dimensions of Account Representative service quality and taxpayer education level on individual taxpayer compliance. The number of taxpayers is increasing from year to year, but this is not matched by taxpayer compliance in paying taxes. The compliance problem is an obstacle in maximizing tax revenue. This study examines the level of compliance of individual taxpayers registered in the West Makassar KPP Pratama area by using several independent variables, namely direct evidence, reliability, responsiveness, assurance, and empathy as dimensions of Account Representative service quality and taxpayer education level. The data used in this study are primary data obtained from the research location, namely through the distribution of questionnaires (list of questions to respondents). The sample consists of 100 respondents who are individual taxpayers as well as secondary data obtained from KPP Pratama West Makassar which is closely related to this research. Data were tested using multiple linear regression analysis. Testing the data using SPSS 20. Researchers also tested the validity and reliability tests for the questionnaire. The classic assumption test used is the multicollinearity test, the normality test, and the heteroscedasticity test. To test the hypothesis, the researcher used the coefficient of determination (R2), simultaneous test (F-test), and partial test (t-test). Based on the results of the analysis carried out, it is concluded that direct evidence, reliability, responsiveness, and assurance have a positive but not significant effect, while empathy has a positive and significant effect, while the level of education has a negative and insignificant effect on individual taxpayer compliance at KPP Pratama Makassar Barat.